Influence of the sFlt-1/PlGF ratio on clinical decision-making in women with suspected preeclampsia – the PreOS study protocol. (February 2015) - Hund, Martin; Verhagen-Kamerbeek, Wilma; Reim, Manfred; Messinger, Diethelm; van der Does, Reinhard; Stepan, Holger
<x xml:space="preserve">Abstract</x> Objective: To assess how routine clinical use of the Roche fully automated Elecsys® sFlt-1/PlGF test changes decision-making of physicians to hospitalize pregnant women with suspected preeclampsia. Methods: The Preeclampsia Open Study (PreOS) study is a multicenter, prospective, open-label, non-interventional study in 150 women showing signs and symptoms of preeclampsia (suspected preeclampsia). Physicians record their intended procedures before and after knowledge of participants' sFlt-1/PlGF ratio. The study is conducted at five investigational sites in Germany and Austria. Conclusion: The PreOS study will provide evidence on how sFlt-1/PlGF ratio testing influences clinical decision-making in women with suspected preeclampsia in real-world clinical practice.